Gastrointestinal Involvement in The Confirmed Covid-19 Patients - Rachma Greta Perdana Putri (Warmadewa University, 2021)
The current pandemic of Coronavirus disease 2019, or known as COVID-19, has been claimed as Public Health Emergency of International Concern by WHO on 30 January 2020. According to WHO, there 47.362.304 confirmed cases and 1.211.986 deaths reported due to COVID-19 and still counting. This article investigates the involvement of gastrointestinal symptoms in COVID-19 related to the pathogenesis, transmission, and severity of the disease. The data was collected by keyword searching through EBSCO, PubMed, Google scholar, and additional references from retrieved articles. This article analyzes studies investigating gastrointestinal symptoms in Covid-19. The studies found gastrointestinal symptoms in COVID-19 confirmed patients such as abdominal pain, diarrhea, nausea, vomiting, constipation, and melena. Two studies showed that COVID-19 patients with gastrointestinal symptoms tended to have more severe disease. ACE2, as the receptor of S protein, was found abundantly in intestinal enterocytes besides in the respiratory system. Enterocyte abnormality induces decreased absorption of NA+, water, and mucosal disaccharides. It leads to increased undigested mono and disaccharides, carbohydrates, fats, and protein into the colon. As a result, the colon is unable to absorb sufficient water, leading to diarrhea. Gastrointestinal symptoms are commonly found in patients with COVIDâ€19, and the trend is increasing in the later stage of the epidemic. SARSâ€CoVâ€2 enters gastrointestinal epithelial cells and the feces of COVIDâ€19 patients are potentially infectious. The virus also found in wastewater system and may cause water pollution. Hence, further studies investigating gastrointestinal symptoms and possibility of fecal oral transmission should be conducted.